PERAN PERKERETAAPIAN DALAM MENUNJANG SISTEM LOGISTIK NASIONAL - Hermanto Dwiatmoko (Jurnal Transportasi, 2018)
Abstract Indonesia is faced with an increasingly high level of international and interregional competition. This competition has shifted from competition between products and companies to competition between logistics networks and supply chains. The logistics process is basically directed to optimize production factors, namely to optimize the costs, time, and quality. The Government of the Republic of Indonesia plans to build 3,250 km of new railway lines during the 5 year administration, in the 2014-2019 period, by constructing the Trans Sumatra, Trans Sulawesi, and Trans Papua railway lines, as well as the double track railway lines in Java. Because rail transport is a mass transportation mode, it is hoped that this railway transportation can reduce national logistics costs. Therefore, railway infrastructure and facilities need to be developed, especially for transporting passengers and goods. Keywords: logistics network, supply chain, rail transportation, national logistics costs  Abstrak Indonesia dihadapkan pada tingkat persaingan antarnegara dan antarregional yang semakin tinggi. Persaingan ini telah bergeser dari persaingan antarproduk dan antarperusahaan ke persaingan antarjaringan logistik dan rantai pasok. Proses logistik pada dasarnya diarahkan untuk mengoptimalkan faktor produksi, yaitu untuk melakukan optimasi terhadap biaya, waktu, dan kualitas. Pemerintah Republik Indonesia mencanangkan akan membangun 3.250 km jalur kereta api baru selama 5 tahun pemerintahan, pada periode  2014-2019, dengan mewujudkan jalur kereta api Trans Sumatera, Trans Sulawesi, dan Trans Papua, serta jalur ganda kereta api di Pulau Jawa. Karena transportasi kereta api merupakan moda angkutan masal, diharapkan angkutan kereta api ini dapat menurunkan biaya logistik nasional. Oleh karena itu, prasarana dan sarana perkeretaapian perlu dikembangkan, khususnya untuk mengangkut penumpang dan barang. Kata-kata kunci: jaringan logistik, rantai pasok, angkutan kereta api, biaya logistik nasional